El teatro como lenguaje artístico y social para dialogar frente a las violencias basadas en género en el marco del XXXII Festival de Mujeres en Escena por la Paz - Ávila Olarte, Juana Valentina (Universidad Antonio Nariño, 2024)
Colombia has been a country that has been involved in an armed conflict (CEV, 2022) But violence is not limited only to rifles; As a society we have normalized deaths, discrimination, individualism, lack of tolerance and other problems that do not allow us that total peace that we so long for. Among the problems mentioned above are gender-based violence of which the majority of women have been victims (CEV, 2022). Due to the capitalist and sexist system in which we become accustomed to living, it is increasingly difficult to generate resistance actions against this violence. As a result of what was mentioned above, this research project arises, which takes the experiences of teachers, actresses, directors, playwrights and artists who meet at the Festival of Women on Stage for Peace (FMEP) in its thirty-second version held in the city of Bogota from August 4 to 13, 2023, to exhibit their artistic presentations, share their experiences and debate issues that concern us as women and as an important part of society